1997
DOI: 10.1097/00006123-199711000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Imaging Study of Extent of Surgical Resection and Prognosis of Malignant Astrocytomas

Abstract: We conclude that the most important prognostic factors affecting survival of patients with anaplastic astrocytomas and glioblastomas multiforme are tumor grade, age, preoperative performance status, and radiation therapy. Postoperative complications adversely affect survival. Aggressive surgical resection did not impart a significant increase in survival time. Surgical resection may improve survival, but its importance is less than that of other factors and may be demonstrable only by larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
2
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(109 citation statements)
references
References 58 publications
2
103
2
2
Order By: Relevance
“…As said above, the difference among these two groups is statistically significant (Mantel-Cox P = 0.0275). These observations confirm literature data (Devaux et al, 1993;Iacoangeli et al, 1993;Kowalczuk et al, 1997), and ensure that the tumour population we are dealing with is representative of the general population of patients suffering from brain tumour that are in the conditions of undergoing surgery. When the survival of these patients is stratified according to MnSOD level in the tumour, a strong link of these levels and prognosis can be observed.…”
Section: Mnsod Content Is An Independent Prognostic Factorsupporting
confidence: 88%
“…As said above, the difference among these two groups is statistically significant (Mantel-Cox P = 0.0275). These observations confirm literature data (Devaux et al, 1993;Iacoangeli et al, 1993;Kowalczuk et al, 1997), and ensure that the tumour population we are dealing with is representative of the general population of patients suffering from brain tumour that are in the conditions of undergoing surgery. When the survival of these patients is stratified according to MnSOD level in the tumour, a strong link of these levels and prognosis can be observed.…”
Section: Mnsod Content Is An Independent Prognostic Factorsupporting
confidence: 88%
“…Several authors declare that patients with higher KPS showed longer survival rather those with lower KPS. 2,6,8,10,14 According to Kreth et al 9 the youngest individuals tend to show higher KPS, which may be considered a confusing variable in the multivariate statistical analysis models. In Lacroix et al series 10 75% of patients showed KPS higher than 80.…”
Section: Discussionmentioning
confidence: 99%
“…3) Tumor volume -Several papers identify the tumor volume as a non-prognostic factor. 8,9,14,21 On the other hand, Jeremic et al 6 mention that tumors smaller than 40 cm 3 show better prognosis. The average tumor volume in Lacroix et al 10 series was 34 cm 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations